Etiological Study of Short Stature among Children Attending Outpatient Department of Pediatrics in a Tertiary Care Medical College Hospital - Imthyas Khan V.H; Harshini B P; Ashoka C; Kumar G V (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Short stature is a term applied to a child whose height is two standard deviations or more below the mean height for children of that gender and chronologic age.Familial short stature and Constitutional Growth delay are considered as normal variants, the pathological short stature includes a wide variety of underlying disorders.Chronic systemic disorders, malnutrition, chromosomal or endocrinal disorders lead to a proportionate short stature.While most of the disproportionate short stature are secondary to skeletal dysplasias or resistant rickets.Etiological evaluation plays an important role in identification of physiological as well as pathological causes of short stature.Subjects and Methods:All children of age between 2 and 18 years with height below 2 standard deviation of mean for age and gender were included in the study. Result:A total of 100 children were studied who fulfilled the criteria of short stature, out of which 61 children were male and 39 were female children.Present study showed that females had more pathological variants (72%) than males (46%) whereas males had more physiological variants (54%) than females (28%) with P-value: 0.011Hypothyroidism was more common in females than males with 28% and 8% respectively. Genetic syndrome was more common in females than males with 10% and 3% respectively. Conclusion:Etiological evaluation is of pivotal role in identification of physiological as well as pathological causes of short stature and also helps in modifying the course of stature by means of early intervention.